2001
DOI: 10.1111/j.1348-0421.2001.tb02650.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution and Purification of Cytolethal Distending Toxin of Actinobacillus actinomycetemcomitans

Abstract: Cytolethal distending toxin (CDT) has been found in various pathogenic bacterial species and causes a cell distending and a G. arrest against eukaryotic cells. All the cdtABC genes, which encode CDT, are known to be required for the CDT activities although the CDT holotoxin structure has not been elucidated. We cloned the cdtABC genes of Actinobacillus actinomycetemcomitans and constructed an Escherichia coli expression system for them. We found that crude extracts from six deletion mutants (~cdtA,~cdtB, &dtC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Although the heterotripartite model of the toxin has been confirmed in multiple cases Oswald et al, 2005;Tóth et al, 2009a;Gargi et al, 2012), there have been cases where the authors reported characteristic CDT activity in the case of CDTs missing either the A or C subunit, as with the CDT produced by Aggregatibacter actinomycetemcomitans (De Rycke et al, 1996;Taieb et al, 2006). The Aggregatibacter CDT was found to be functional, albeit with a reduced titre, when lacking the A (Akifusa et al, 2001) or the C subunit (Saiki et al, 2001). These findings were later explained by the work of Damek-Poprawa et al (2012) who reported that after the internalisation of CdtB, CdtA remains on the cell surface, while CdtC migrates into the cytosol, suggesting that it acts as a chaperone to CdtB.…”
Section: Discussionmentioning
confidence: 99%
“…Although the heterotripartite model of the toxin has been confirmed in multiple cases Oswald et al, 2005;Tóth et al, 2009a;Gargi et al, 2012), there have been cases where the authors reported characteristic CDT activity in the case of CDTs missing either the A or C subunit, as with the CDT produced by Aggregatibacter actinomycetemcomitans (De Rycke et al, 1996;Taieb et al, 2006). The Aggregatibacter CDT was found to be functional, albeit with a reduced titre, when lacking the A (Akifusa et al, 2001) or the C subunit (Saiki et al, 2001). These findings were later explained by the work of Damek-Poprawa et al (2012) who reported that after the internalisation of CdtB, CdtA remains on the cell surface, while CdtC migrates into the cytosol, suggesting that it acts as a chaperone to CdtB.…”
Section: Discussionmentioning
confidence: 99%
“…CDT activity is dependent on the expression of three closely linked genes, cdtA, cdtB, and cdtC, encoding proteins with molecular masses of approximately 27, 29, and 20 kDa, respectively (1,9,19,23,25,28). Several reports show that the CDT holotoxin is composed of all three proteins bound together to from a tripartite complex (9,13,15,22,24). Considerable evidence supports the notion that CdtB is the biologically active subunit.…”
mentioning
confidence: 93%
“…The protein products of the individual cdt genes of H. ducreyi are most similar (i.e., Ͼ90% identity) to those of Actinobacillus actinomycetemcomitans (18). The calculated molecular weights of the mature form of these three proteins are as follows: CdtA, 22,855; CdtB, 28,955; and CdtC, 18,356. There is now considerable evidence to indicate that the CDT holotoxin, at least for H. ducreyi (9), Campylobacter jejuni (14), and A. actinomycetemcomitans (1,17,27), is comprised of CdtA, CdtB, and CdtC bound together to form a tripartite toxin. Determination of the function of the individual cdt gene products has proven challenging, however.…”
mentioning
confidence: 99%
“…No cytotoxicity has been attributed to the CdtA protein to date, regardless of the organism from which it was cloned or purified (1,9,9,14,17,27). However, it was recently reported that CdtA from A. actinomycetemcomitans binds to the surface of Chinese hamster ovary (CHO) cells, and it was suggested that this protein works alone to bind the CDT holotoxin to the eukaryotic cell surface (17), although it has also been proposed that CdtA and CdtC form a complex which is required for the delivery of CdtB into the eukaryotic cell (14,15).…”
mentioning
confidence: 99%